2019
DOI: 10.1515/jpem-2019-0226
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA 196a2 expression and miR-196a2 (rs11614913) polymorphism in T1DM: a pilot study

Abstract: Background Recent emerging evidence supports the role of miR-196a2 in various human diseases. However, its role in type 1 diabetes mellitus (T1DM) is still underestimated. We aimed, for the first time, to investigate the expression of miR-196a2 in T1DM and the association of miR-196a2 (rs11614913) polymorphism with susceptibility of T1DM in a sample of patients from Cairo, Egypt. Methods The study included 150 patients and 150 healthy subjects. Evaluation of rs11614913 genotypes and miR-196a2 expression was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…A previous study has shown that miR-196a rs11614913 T/C is linked with T2DM [ 29 ]. Downregulation of its mature miRNA may play a pivotal role in T1DM [ 44 ]. In the current study, we found that the genotype TT (n = 76/22.4%) of rs11614913 T/C was more frequent in cases as compared to controls (n = 33/13.98%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that miR-196a rs11614913 T/C is linked with T2DM [ 29 ]. Downregulation of its mature miRNA may play a pivotal role in T1DM [ 44 ]. In the current study, we found that the genotype TT (n = 76/22.4%) of rs11614913 T/C was more frequent in cases as compared to controls (n = 33/13.98%).…”
Section: Discussionmentioning
confidence: 99%
“…The study stated that the association of the TT genotype with T1DM remained significant. The study also reported decreased relative expression of miR-196a2 in patients compared to controls [ 44 ]. In contrast to our studies, some researchers have reported a higher frequency of T alleles in patients than controls and the T allele has been reported to decrease the risk of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…miR-146a/rs2910164 was associated with the non-syndromic orofacial cleft (Pan et al, 2018) and bladder cancer (Wang et al, 2012). miR-196a2/rs11614913 showed an association with the hepatocellular carcinoma (Zheng et al, 2017) and type 1 diabetes mellitus (Ibrahim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated the role of miRNAs-relates SNPs in the incidence and prognosis of T1DM. For instance, miR-196a rs11614913 is reported to be associated with the pathogenesis of T1DM (13).…”
Section: -Discussionmentioning
confidence: 99%
“…Studies have vastly reported that SNPs in the miRNAs coding genes can affect the binding a nity and binding ability of the miRNAs and even can alter the target mRNA (12). miRNAs-related SNPs are known to be associated with the incidence of several diseases including T1DM (13). Limited studies have investigated the association between miR-21 rs1292037 SNP and human-related diseases to this date.…”
Section: -Backgroundmentioning
confidence: 99%